Surgical repositioning of an impacted and dilacerated central incisor: A case report/ Annapurny Venkiteswaran, Ha Kien Onn and Sabri Musa - Venkiteswaran, Annapurny; Ha, Kien Onn; Musa, Sabri (Faculty of Dentistry, 2016)
This case report describes the management of an impacted and dilacerated upper permanent incisor in an 11 year old girl who also presented with a congenitally missing lateral incisor in the same quadrant. The two treatment options commonly chosen for the management of an impacted incisor are surgical exposure followed by orthodontic traction and extraction of the tooth itself. This case posed an extra challenge as the adjacent lateral incisor was congenitally missing. Instead of resorting to the use of dentures, an alternative treatment involving the surgical repositioning of the impacted tooth was done. This method not only satisfied the patient’s aesthetic requirement but ensured preservation of alveolar bone height and thickness in the upper anterior segment. Surgical repositioning of an impacted and/or dilacerated tooth can be considered as an alternative treatment option when surgical exposure and traction of the tooth is not possible.